Peer cooperation during teaching in paired field placements: Forms and challenges - Do, Minh-Ly; Hascher, Tina (Frontline Learning Research, 2023)
Paired field placement is an important element of teacher education where student teachers can acquire professional cooperative skills through team teaching. However, little is known about challenges that student teachers face during team teaching. Also, knowledge about challenges during the team teaching process (e.g. planning, instruction, reflection) is scarce. This study focuses on pre-primary and primary student teachers’ challenges with peer cooperation during team teaching, the problems they face and how they cope with negative experiences. Data was collected from 30 student teachers through in-depth, semi-structured interviews. Results reveal various forms of conflict during different phases of peer cooperation in team teaching such as lack of flexibility due to pressure to follow agreements, or unclear roles and responsibilities. Instruction turns out to be the most challenging phase of team teaching, with lack of compatibility with the peer as the most frequent reason for problems. Reflection is rarely used as a cooperative setting. The findings also revealed the frequent use of reactive strategies to cope with challenges, particularly the strategy of avoiding problems.